PENDIDIKAN MULTIKULTURAL DI INDONESIA SEBUAH PANDANGAN KONSEPSIONAL - Dede Rosyada (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2014)
This article was written to provide an overview of the conceptual view of multicultural education inIndonesia. In order to obtain data on the concept of multicultural authors conducted a study of literatures. As we know that Indonesia is a country with ethnic diversity but it aspires to the same goal, that is to the wealthy and prosperous society. Therefore, it becomes important to develop multicultural education, which is an educational process that gives equal opportunities to all children including minorities regardless of their differences in ethnicity, culture and religion, to strengthen the unity and integrity, national identity and the nation’s standing in the international world. In this case, the school must design the learning process, preparing curriculum and evaluation design, as well as prepare teachers who have the multicultural perception, attitude and behavior, so that they becomes part of those make a signifi cant contribution to the development of multicultural attitude of the students.